2017
DOI: 10.1021/acs.jpcc.7b05582
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ultrafast Photophysical Pathways in Photoexcited Organic Heterojunctions

Abstract: The exciton dissociation and charge separation occurring on subpicosecond time scales following the photoexcitation are studied in a model donor/acceptor heterojunction using a fully quantum approach. Higher-than-LUMO acceptor orbitals which are energetically aligned with the donor LUMO orbital participate in the ultrafast interfacial dynamics by creating photon-absorbing chargebridging states in which charges are spatially separated and which can be directly photoexcited. Along with the states brought about b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 71 publications
0
27
0
Order By: Relevance
“…In addition to the MH, LJH and TCH theories, there are a number of other approaches that investigate the influence of phonons on the properties of organic solar cells. These are, among others [33,34], based on Ansatz wave functions [35], a dynamics controlled truncation scheme within the density matrix formalism [36], Green's function formalism [37] or the quantum master equation [38]. Despite their success in describing some of the aspects characteristic for electron-phonon coupled systems, these approaches usually suffer from the curse of dimensionality, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the MH, LJH and TCH theories, there are a number of other approaches that investigate the influence of phonons on the properties of organic solar cells. These are, among others [33,34], based on Ansatz wave functions [35], a dynamics controlled truncation scheme within the density matrix formalism [36], Green's function formalism [37] or the quantum master equation [38]. Despite their success in describing some of the aspects characteristic for electron-phonon coupled systems, these approaches usually suffer from the curse of dimensionality, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the normalized PL intensity was the lowest in the “NiO x via B-OH” samples. This suggests that the exciton dissociation (or charge separation) tendency of this material is superior [78,79,80,81]. It was also found that the PCE (%) values of the devices were consistent with this tendency (Table 1).…”
Section: Resultsmentioning
confidence: 60%
“…Let us point out another viewpoint on the result embodied in Eq. (34). Equation ( 33) can be formally rewritten by introducing the dipole-moment hyperoperators that act the initial electronic state |g g| from the opposite sides…”
Section: General Theory Of Second-order Light-induced Dynamicsmentioning
confidence: 99%
“…The manipulations that are necessary to recast Eqs. ( 40) and (34) as HEOM presented in Eqs. ( 19) and ( 20), respectively, proceed as usually [48].…”
Section: Excitation By Weak (Coherent) Laser Pulsesmentioning
confidence: 99%
See 1 more Smart Citation